MALDI imaging reveals lipid changes in the skin of leprosy patients before and after multidrug therapy (MDT). (17th November 2015) - de Macedo, Cristiana S.; Anderson, David M.; Pascarelli, Bernardo M.; Spraggins, Jeffrey M.; Sarno, Euzenir N.; Schey, Kevin L.; Pessolani, Maria Cristina V.
Abstract : Leprosy still represents a health problem in several countries. Affecting skin and peripheral nerves, it may lead to permanent disabilities. Disturbances on skin lipid metabolism in leprosy were already observed; however, the localization and distribution of lipids could not be accessed. The role of lipids on infectious disease has been fully addressed only recently, as they directly influence immune response. Matrix‐assisted laser desorption/ionization imaging mass spectrometry provides a powerful tool to localize and identify lipids in tissues. The aim of this work was to study and compare the changes in lipid distribution of skin biopsies taken from leprosy patients before and after multidrug therapy (MDT). Different species of phosphatidic acid, phosphatidylethanolamine, phosphatidylserine, phosphatidylinositol, sphingomyelin and phosphatidylcholine were detected. Differences in skin lipid signal intensities, as well as in their localization, were observed before and after MDT in every patient. In general, lipid distribution in the skin after MDT had a pattern similar to control skin samples, where most of the lipids were located in the upper part of the dermis and epidermis. This study opens paths to a better understanding of lipid functions in leprosy pathogenesis and immune response. Copyright © 2015 John Wiley & Sons, Ltd.